A conceptualization of smart library in Indonesia - Djoko Sigit Sayogo; Sri Budi Cantika Yuli; Wiyono Wiyono; Shiho Sawai (Journal of Innovation in Business and Economics, 2020)
Even with the increasing relevance of a smart public library in the fast-paced environment like nowadays, a standardized definition of the term smart library is, in fact, still open for discussion, specifically in a developing country. This study aims to define the conceptualization of a smart library in developing countries. A case study encompassing documentation analysis and in-depth interviews with nine public officials at the Regency of Bojonegoro, Indonesia, was used to collect data. This study showcase that a smart library started from the innovative and inventive programs and services geared toward achieving the library as a place for the co-production of knowledge. Likewise, our findings further demonstrate that technology per se is not the most critical challenge for a smart library as compare to organizational, policies and regulations, and political issues in the case of a developing country. Thus, a smart library in Indonesia intensifies more effort to pursue smart services first, followed by smart governance, smart people, and smart place, respectively.